Tunneling luminescence in long lasting afterglow of SrAl2O4:Eu,Dy - Liepina, Virginija; Millers, Donats; Smits, Krisjanis (Elsevier B.V., 2017)
A long lasting (afterglowing) luminescent material SrAl2O4: Eu2+, Dy3+ was prepared by high temperature solid-state reaction method. The processes responsible for long lasting luminescence were studied by means of luminescence spectra, thermally stimulated luminescence and afterglow kinetics. Two processes are found to contribute in excited Eu 2+ creation – the thermally released electrons recombination and electron tunneling from trap to Eu3+. The possible scheme of long lasting luminescence mechanism is proposed.
The publication is prepared with the ﬁnancial support of National Research Programme IMIS2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Long afterglow; Luminescence; Rare earth